Prevalence of metabolic syndrome and associated factors in Yobe state provence of Nigeria - Likita, Musa Audu (2014)
Metabolic syndrome (MetS) is a clustering of interrelated cardiovascular risk factors of metabolic origin that are associated with the development of cardiovascular diseases and type II diabetes mellitus. The objective of the study was to determine the prevalence of the MetS and associated risk factors among civil servants in Yobe state, Nigeria. A cross sectional study was conducted between September 2012 and January 2013, using a stratified multi stage cluster sampling design. Biomedical (fasting blood glucose and lipid profile), anthropometry, blood pressure and questionnaire based risk factors were assessed. Metabolic syndrome was defined according to the International Diabetes Federation (IDF). Multivariate models were used to study the association between independent risk factors and the prevalence of the MetS. Out of the 500 respondents, 445 agreed to participate in the study giving a response rate of 89%. The prevalence of MetS was 36.4% among Yobe state civil servants and was significantly higher in females (45.9%) as compared to 31.3% in males (p = 0.002). The prevalence of MetS increased significantly with age in both gender, ranging from 19.7% to 48.1% in males and 46.6% to 60.0% in females. The most frequently observed metabolic features were increased waist circumference 51.7% (women 81.5% and men 35.1%), high blood pressure 46.3% (females 49.7% and males 44.4%), elevated fasting blood glucose 48.8% (males 44.4%, and females 40.1%), high triglycerides 48.5% (males 58.3% females 37.5%), whereas low high density lipoproteins cholesterol was observed to be less (13.0 %) frequent (females 15.3%, and males 12.5%). Adjusted odds ratio (OR) showed that gender, age, monthly income, education, tobacco use, alcohol consumption, family history of hypertension, diabetes and obesity and physical inactivity were significantly associated with MetS. The odds of females having MetS were 4.25 times higher compared to males (OR= 4.225; 95% CI 2.441 - 7.315). Respondents aged 50 years and above had more than two fold increased risk of MetS compared to younger age (OR= 2.23; 95% CI 1.071 - 4.637). Respondents with a family history of hypertension, diabetes and/or obesity were six times at risk of having MetS (OR= 6.228; 95%CI 3.614 - 10.732) compared to those that do not have such family history. Tobacco users were more than four times at high risk of having MetS than those that never used tobacco (OR= 4.563; 95%CI 2.449 - 8.502), P<0.001. Similarly heavy alcohol drinkers were found to have four times odds of having MetS than the non-alcohol drinkers (OR= 4.271; 95%CI 1.994 - 9.144). This study indicated that low level of physical activity is 16 times increased risk of metabolic syndrome (OR=16.23; 95%CI 5.945 - 44.33). This study indicated that the prevalence of the MetS among Yobe state civil servants is high. Longitudinal studies are required to establish true cause of metabolic syndrome in Yobe state. Early identification of MetS and interventions are important strategies in prevention and control of diabetes, cardiovascular diseases in Yobe state.